The presentation of the pattern of creativity management with social capital approach in the local media of Esfahan - Shirin Tabrizi; Faezeh Taghipour; Saeed Sharifi; Hamid Davazdah emami (Religion & Communication)
The aim of this study is to present a model of creative management with a social capital approach in Broadcasting based on the framework of the tradition of qualitative research using the Strauss - Corbin 's underlying theory approach. Based on the principle of theoretical saturation, semi - structured interview was conducted from 12 experts in the study area whom selected by using purposive sampling method. External auditors were used to assess the validity of the data. The analysis was performed inductively with open and axial coding. Results in the form of a paradigm model include: causal conditions ( active consumer - oriented audience , transformational organization, nature of information, audience attention management, environmental uncertainty ) axial phenomenon ( creative management with social capital approach ) , contextual conditions (ecological creative engineering, social capital Creativity , team building , technological capital, motivation and attitude ) , interventionist conditions ( commitment to heritage, creative talent, individual independence , human resource competence and managerial responsibilities ) Strategies ( discovering and attracting creativity , developing and strengthening creativity , and supporting and recreating creativity ) , And consequences ( social capital, creative citizen , creative class, and creative resources ) .